Teknologi Informasi dan Kualitas Layanan Mempengaruhi Tingkat Kepuasan Nasabah Bank Syariah - Fauzul Azhar; Azharsyah Ibrahim; Akmal Riza (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2022)
This study aims to determine the effect of information technology and service quality on customer satisfaction at BNI Syariah Banda Aceh Branch Office. Quantitative research method with multiple linear regression analysis using IBM SPSS software version 25. The results showed that information technology and service quality variables had a positive and significant effect on customer satisfaction at BNI Syariah Banda Aceh Branch Office. customer satisfaction variable can be explained by information technology and service quality variables 53.6%, while the effect is influenced by other variables outside the study.